PERANCANGAN SISTEM TRANSMISI CHAIN AND SPROCKET UNTUK PENGEMBANGAN MEDIA PENDIDIKAN DAN PENELITIAN KENDARAAN LISTRIK - WARSONO, WARSONO ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The development of electric vehicle technology in today's increasingly fast growing, electric vehicles or electric Vehicle is one of the options that are environmentally friendly transportation alternative cheap and does not produce air pollution. The design of the transmission system with a chain and sprocket on the electric bicycle is a technology that is simple, does not pollute the environment more energy efficient at an affordable price by various groups and environmental (sustainability development). This technology is designed for a particular community in order to adapt to the environmental aspects, and economic communities concerned and the prospects for future development. Chain-sprocket transmission system in electric bicycles is expected to cover a longer distance and efficient use of the battery. This study is divided into two stages, the first stage is to design the front as the driving sprocket rear sprocket with the initial condition at the time dikayuh front sprocket to the rear between the chain and its sprockets will be modified into a free spins round to the back wheel in addition to the front sprocket will be moved by sprocket is located in the motor armature thus driving the front sprocket is in double electric bicycle as a driver and the driven. The second stage is the change of the bike paddle combined with the motor armature as driving, using motor armature voltage 24 volt DC power of 350 watts, the battery voltage is 24 volts with a current of 14.4 amperes. Transmission with three speed levels with changes in the number of teeth is in the very back and blend with the rear wheel. The design of chain and sprocket transmission system can produce a torque of 4.22 Nm at the rate of first speed level is used to start the vehicle started way early. At speeds above 20 km / h torque of 2.46 is achieved with three speed levels. Comparison with the same time the distance between one and three speed levels is 7.10 km distance assuming the speed of 10 km / h to 25 km / h is the maximum speed attained level one and three speed is 14.3 km / h and 41.7 km / hours.